Effects of COVID-19 lockdown on heart rate variability - Bourdillon, N.; Yazdani, S.; Schmitt, L.; Millet, G.P. (PLOS ONE, 2020)
Introduction: Strict lockdown rules were imposed to the French population from 17 March to 11 May 2020, which may result in limited possibilities of physical activity, modified psychological and health states. This report is focused on HRV parameters kinetics before, during and after this lockdown period.